2002
DOI: 10.1074/jbc.m201949200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/Calmodulin-dependent Protein Kinase II Phosphorylates and Regulates the Drosophila Eag Potassium Channel

Abstract: Modulation of neuronal excitability is believed to be an important mechanism of plasticity in the nervous system. Calcium/calmodulin-dependent protein kinase II (CaMKII) has been postulated to regulate the ether à go-go (eag) potassium channel in Drosophila. Inhibition of CaMKII and mutation of the eag gene both cause hyperexcitability at the larval neuromuscular junction (NMJ) and memory formation defects in the adult. In this study, we identify a single site, threonine 787, as the major CaMKII phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 26 publications
2
80
1
2
Order By: Relevance
“…Activated CaMKII phosphorylates the synaptic MAGUK protein DLG, causing release of FAS2 from its synaptic scaffold and subsequent modulation of synaptic growth in Drosophila (32,33). In addition, CaMKII activation also regulates the activity of the ether-a-go-go (eag) family of potassium channels in Drosophila, altering aspects of nerve excitability that could contribute to synaptic growth (48,49). Intracellular calcium levels directly regulate cAMP signaling through the activation of adenylate cyclase by calmodulin (50), enhancing cAMPdependent pathways implicated in synaptic growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Activated CaMKII phosphorylates the synaptic MAGUK protein DLG, causing release of FAS2 from its synaptic scaffold and subsequent modulation of synaptic growth in Drosophila (32,33). In addition, CaMKII activation also regulates the activity of the ether-a-go-go (eag) family of potassium channels in Drosophila, altering aspects of nerve excitability that could contribute to synaptic growth (48,49). Intracellular calcium levels directly regulate cAMP signaling through the activation of adenylate cyclase by calmodulin (50), enhancing cAMPdependent pathways implicated in synaptic growth (12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that EAG is phosphorylated by CaMKII activity endogenous to the oocytes even at basal calcium levels (Wang et al, 2002). Both the increase in current amplitude and the changes in inactivation in the presence of CMG are reminiscent of the changes in current observed as a consequence of phosphorylation.…”
Section: Cmg Modulates Eag Currentmentioning
confidence: 67%
“…eag larvae exhibit spontaneous action potentials in the motor nerve and excitatory junctional potentials in muscle that are broadened compared with those of wild-type larvae (Ganetzky and Wu, 1985). EAG is present in the axons and terminals innervating the larval body-wall musculature (Wang et al, 2002) and is localized with synaptobrevin in the CNS (Sun et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the NMJ, CaMKII regulates presynaptic excitability and plasticity Park et al, 2002). One mechanism by which excitability can be regulated is by modulation of potassium channels, including the EAG protein Wang et al, 2002). Postsynaptic CaMKII has a role in regulation of Dlg and FasII localization (Koh et al, 2000;Fig.…”
Section: Calciummentioning
confidence: 99%